Răspuns :
a) (2012+x)-(2012-x)=2012+x-2012+x=4024+2x
b) (2015+x)-(1015-x)=2015+x-1015+x=3030+2x
P.S: minusul in fata unei paranteze schimba toate semnele din acea paranteaza
b) (2015+x)-(1015-x)=2015+x-1015+x=3030+2x
P.S: minusul in fata unei paranteze schimba toate semnele din acea paranteaza
a) (2012+x)-(2012-x)=
2x=2012+2012=
2x=4024
x=4024:2=
x=2012
b) (2015+x)-(1015-x)=
2x=2015-1015=
2x=1000
x=1000:2=
x=500
2x=2012+2012=
2x=4024
x=4024:2=
x=2012
b) (2015+x)-(1015-x)=
2x=2015-1015=
2x=1000
x=1000:2=
x=500